30 × 30 pledge to increase female officer representation by 2030. Issue 6 (19th September 2021) - Sutton, Halley
Abstract : The University of Utah Police Department has undertaken a pledge to increase diversity in its recruitment and retention of officers. "Just like every other law enforcement agency in the country, we have a huge problem with attracting and retaining employees, " Jason Hinojosa, Deputy Chief of the University of Utah Police Department, said. That challenge has only increased in the wake of the death of George Floyd. "There's been a lot of negative press, a lot of stress, and less interest in law enforcement [as a career], " Hinojosa said.